Analysis of economic management problems and challenges in increasing investment in the upstream oil and gas industry - Donna Betty (Jurnal Mantik, 2024)
Oil and gas is a very important industry in economic circulation which can contain the course of economic stability. In the oil and gas industry sector, it will really need the role of investors to provide funds in order to carry out oil and gas exploration and exploitation in accordance with the target. In this study using phenomenological qualitative research methods based on explanations related to facts that exist during the research process. The facts obtained from the analysis of problems and challenges of investment in the oil and gas industry will be presented qualitatively in accordance with the existing facts. In qualitative methods that describe related research objects that will provide meaning related to findings in the phenomenological category. This research was supported by the acquisition of data derived from focus group discussions (FGDs) conducted by the Expertise Agency with SKK Migas and the Ministry of Energy from Mineral Resources. The result of this study is that many factors that can affect upstream oil and gas investment are influenced by internal and external factors which must be overcome as a whole.